Foreign direct investment and real gross domestic product: analysis of empirical evidence from sri lanka - Kengatharan, L.; Jeyan Suganya, D.F. (University of Sri Jayewardenepura, 2022)
Foreign Direct Investment is one of the crucial forms of international equity flows for having undeniable growth in gross domestic product among emerging countries. The main objective of the study is to investigate the empirical relationship between foreign direct investment and real gross domestic product in Sri Lanka. Net foreign direct inflow was considered as the independent variable while real gross domestic product was considered as the outcome variable in this study. However, Exchange rate and money supply were selected as the control variables on the relationship between foreign direct investment and real gross domestic product. The current study used annual time series data over the period from 1970 to 2019 which were collected from the annual reports of the Central Bank of Sri Lanka. Stationary of the data was tested using the Augmented Dickey-Fuller test. Johansen co-integration rank test, max Eigen value test, Vector Error Correction (VEC) were used to estimate the relationship between foreign direct investment and real gross domestic product. At the 5% level of significance, the co-integration rank test and max Eigen value test revealed that there is only one co-integration equation existing in the study. Therefore, it was concluded that foreign direct investment has long run impact on economic growth. Likewise, VEC revealed that foreign direct investment, exchange rate and money supply cause real GDP in the short run. The results support the theoretical prediction that foreign direct investment would play an active role in economic growth as it positively leads to the GDP. The study, therefore, concludes that foreign direct investment is driving the economic growth in Sri Lanka.
Keywords: Foreign Direct Investment; Economic Growth; Vector Error Correction Model; Sri Lanka